PENERAPAN SYSTEM USABILITY SCALE DAN USER-CENTERED DESIGN PADA PENGUJIAN PLATFORM PEMBELAJARAN DIGITAL - Dewinta, Virgie Melky; Ikhwani, Muhammad; Ula, Mutamimmul (Jurnal Teknik Informasi dan Komputer (Tekinkom), 2025)
The digital transformation in education has accelerated the use of online learning platforms such as Ruangguru. However, the quality of the user interface (UI) plays a crucial role in determining user comfort and application effectiveness. This study aims to evaluate and improve the interface design of the Ruangguru application by applying the System Usability Scale (SUS) method and the User-Centered Design (UCD) approach. SUS was used to measure usability based on user perceptions, while UCD guided the redesign process to align with the needs and characteristics of users from elementary, junior high, and senior high school levels. Initial testing showed an average SUS score of 35, which falls into the Not Acceptable category. After redesigning the interface using UCD principles, the follow-up test showed an improved SUS score of 57, categorized as Marginal Usability. This increase reflects a notable improvement in user experience, although it has not yet reached the optimal level. Therefore, the implementation of SUS and UCD proved effective in identifying design issues and offering solutions tailored to user needs. The findings provide a solid foundation for further development of more user-friendly and inclusive digital learning platforms.